New host association for Sirex noctilio and Amylostereum areolatum on Cedrus atlantica - Burnip, G.M.; Harvey, I.C.; Voice, D.; Braithwaite, M. (New Zealand Plant Protection, 2008)
Wood boring larvae considered to be Sirex wood wasp were found together with its symbiot the pathogenic Amylostereum fungi associated with ca 20 dead and dying cedar trees at a Christchurch golf club MAF Biosecurity New Zealand was contacted because it was thought that the Sirex was possibly a species not present in New Zealand such as Sirex juvencus or Urocerus gigas (both high impact forest pests) since the single Sirex species present here (Sirex noctilio) had not previously been recorded attacking Cedrus sp (cedar) in New Zealand or elsewhere Furthermore if the Sirex was a recent incursion of a new to New Zealand species the Amylostereum fungi might also have been an exotic species Further examinations revealed a single adult Sirex (live preemergence) within a larval tunnel This allowed definitive morphological identification as Sirex noctilio the species already present in New Zealand Molecular diagnostics (direct sequencing) determined the fungi to be Amylostereum areolatum; the Amylostereum fungi commonly found in association with Sirex noctilio in New Zealand Pinus spp Investigations suggest tree stress (probably nontarget herbicide impacts) resulted in the cedar becoming susceptible to Sirex noctilio attack This represents a new record of association between Sirex noctilio and Amylostereum areolatum on Cedrus atlantica host